The Impact of Mobile Service Quality and Brand Image on Customer Loyalty - Ribka Astasari Mulyono; Lamhot Henry Pasaribu (Enrichment : Journal of Management, 2021)
The purpose of this study is to examine whether mobile service quality and brand image have positive impact on customer loyalty with customer satisfaction as intervening (mediating) variable. The survey method used in this study. Data collection was carried out using a questionnaire instrument to respondents has been using service from GoFood Mobile Application in Jabodetabek, Yogyakarta, Surabaya, Bandung and Makassar. The sampling technique was carried out by convenience sampling. The approach used is Partial Least Square-Structural Equation Modeling using the SmartPLS 3.0 program. The results showed that mobile service quality and brand image had a positive impact on customer loyalty with customer satisfaction as intervening variable.